Biomechanical parameters of the golf swing associated with lower back pain: A systematic review - Watson, M.; Coughlan, D.; Clement, N. D.; Murray, I. R.; Murray, A. D.; Miller, S. C. (Journal of Sports Sciences, 2023)
Low back pain (LBP) is the most common injury in golfers of all abilities. The primary aim of this review was to improve understanding of human golf swing biomechanics associated with LBP. A systematic review using the PRISMA guidelines was performed. Nine studies satisfying inclusion criteria and dually reporting golf swing biomechanics and LBP were identified. Human golf swing biomechanics potentially associated with LBP include: reduced lumbar flexion velocity; reduced transition phase length; reduced lumbar torsional load; earlier onset of erector spinae contraction; increased lumbar lateral flexion velocity; reduced or greater erector spinae activity; and earlier onset of external oblique contraction. These potential associations were undermined by a very limited and conflicting quality of evidence, study designs which introduced a severe potential for bias and a lack of prospective study design. There is no conclusive evidence to support the commonly held belief that LBP is associated with "poor" golf swing technique. The potential associations identified should be further investigated by prospective studies of robust design, recruiting participants of both sexes and dexterities. Once firm associations have been identified, further research is required to establish how this knowledge can be best integrated into injury prevention and rehabilitation.